The role of flexibility in shaping teachers’ digital learning agility: a preliminary study - Mohd Rosli, Nur Dania; Abdullah, Kamilah; Md. Khambari, Mas Nida; Su, Luan Wong; Zakaria, Noor Syamilah; Moses, Priscilla; Hamzah, Siti Raba’ah (Asia-Pacific Society for Computers in Education (APSCE), 2023)
Digitally agile teachers are capable to deal with new experience flexibly and rapidly by trying new behaviors and making quick adjustment so that learning can take place even they have constraints especially in using technologies. Flexible teachers are capable to adjust their plan on the fly and make changes to suit current demand. This preliminary study explores the role of flexibility in supporting teachers’ digital learning agility. The study employed qualitative approach with three in-service teachers through semi-structured interviews. Findings suggest that flexibility helped teachers to become digitally agile by developing more effective and strategic behaviors to overcome difficulties in online learning. This study emphasizes the value of flexibility in enhancing teachers' digital learning agility and offers suggestions for personal and professional development.